Factors Affecting the Length of Stay in the Intensive Care Unit: Our Clinical Experience - Toptas, Mehmet (Biomed Res Int, 2018)
BACKGROUND AND AIM: Long hospital days in intensive care unit (ICU) due to life-threatening diseases are increasing in the world. The primary goal in ICU is to decrease length of stay in order to improve the quality of medical care and reduce cost. The aim of our study is to identify and categorize the factors associated with prolonged stays in ICU. MATERIALS AND METHOD: We retrospectively analyzed 3925 patients. We obtained the patients' demographic, clinical, diagnostic, and physiologic variables; mortality; lengths of stay by examining the intensive care unit database records. RESULTS: The mean age of the study was 61.6 ± 18.9 years. The average length of stay in intensive care unit was 10.2 ± 25.2 days. The most common cause of hospitalization was because of multiple diseases (19.5%). The length of stay was positively correlated with urea, creatinine, and sodium. It was negatively correlated with uric acid and hematocrit levels. Length of stay was significantly higher in patients not operated on than in patients operated on (p < 0.001). CONCLUSION: Our study showed a significantly increased length of stay in patients with cardiovascular system diseases, multiple diseases, nervous system diseases, and cerebrovascular diseases. Moreover we showed that when urea, creatinine, and sodium values increase, in parallel the length of stay increases.